Analisis Bibliometrik dan Vosviewer Dampak Demokrasi Ekonomi: Penegakan Hukum Persaingan Bisnis di Indonesia - Sahib, Welly Anwar Rulhaq; Khaeroni, Rian (Fakultas Hukum Universitas Nahdltul Ulama Cirebon, 2022)
This study aims to investigate the impact of economic democracy on the enforcement of competition law in Indonesia through a bibliometric analysis approach and VOSviewer. By utilizing bibliometric methods, this study identifies current research trends involving economic democracy and competition law enforcement in Indonesia. The application of VOSviewer provides a comprehensive visualization of the relationship and development of key topics in the literature. The findings of the study are expected to provide in-depth insights into the complex dynamics between economic democracy and competition law enforcement in the Indonesian context. The approach method involves bibliometric analysis by focusing on scientific publications, including journal and conference articles, related to the relationship between economic democracy and competition law enforcement at the national level. By exploring relevant literature, this study makes an important contribution to an in-depth understanding of recent developments in this research. The results of the VOSviewer analysis also provide a useful visualization to understand the network of concepts and key topics related to the impact of economic democracy on competition law enforcement in Indonesia.